2020
DOI: 10.3389/fpsyt.2020.570727
|View full text |Cite
|
Sign up to set email alerts
|

Parental Birth-Related PTSD Symptoms and Bonding in the Early Postpartum Period: A Prospective Population-Based Cohort Study

Abstract: The parent-infant bond following childbirth is an important facilitator of optimal infant development. So far, research has mainly focused on mother-infant bonding. Data on fathers are still sparse. Parental mental health, such as posttraumatic stress symptoms (PTSD), may influence mother-infant relations and/or interactions. There is evidence that both parents can experience PTSD symptoms following childbirth (PTSD-CB). The aim of this study is to investigate the prospective relationship between parental PTSD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 38 publications
1
33
0
Order By: Relevance
“…The incidence of PTSD reported in this study is broadly consistent with previous reports in other patient populations [22]. Unlike other patients, however, the effect of PTSD is not just limited to the mother but also extends to her offspring; post-partum PTSD is associated with failed initiation of breastfeeding, a negative impact on the social-emotional development of children at 2 years of age, and arguably, impaired maternal-infant bonding [23][24][25]. Therefore, early recognition of AAGA and subsequent intervention is paramount to minimising the long-term consequences for the mother-infant dyad.…”
Section: Consequencessupporting
confidence: 88%
“…The incidence of PTSD reported in this study is broadly consistent with previous reports in other patient populations [22]. Unlike other patients, however, the effect of PTSD is not just limited to the mother but also extends to her offspring; post-partum PTSD is associated with failed initiation of breastfeeding, a negative impact on the social-emotional development of children at 2 years of age, and arguably, impaired maternal-infant bonding [23][24][25]. Therefore, early recognition of AAGA and subsequent intervention is paramount to minimising the long-term consequences for the mother-infant dyad.…”
Section: Consequencessupporting
confidence: 88%
“…These findings could mean that depressed mothers perceive their infant as more difficult ( McGrath et al, 2008 ). Furthermore, they may indicate that the mother’s personal feelings of birth trauma, represented here by negative birth and postnatal emotional states, such as Anxious-Afraid, Neglected and Postnatal Distress, contribute equally to PPD and CB-PTSD, with an adverse impact on mother–infant bonding ( Stuijfzand et al, 2020 ), in turn affecting infant temperament. Alternatively, a challenging birth experience could lead directly to increased unsettled infant behaviour via physiological pathways, as discussed.…”
Section: Discussionmentioning
confidence: 99%
“…78 As well, parents of medically fragile infants who were admitted to the NICU may feel emotionally distant from their infants, 79 as a result of their acute grief response to their child's medical diagnosis. 80 Traumatic birth and non-vaginal births have also been associated with challenges in maternal bonding [81][82][83] that may reflect some avoidance of the infant as they may serve as a reminder of the birth trauma. While grief was not directly assessed, previous work on widescale trauma found that mothers exposed to war trauma had lower levels of emotional availability.…”
Section: Discussionmentioning
confidence: 99%